Implementation Of Proportional, Integral And Derivative(Pid) Terms For Thermal Management Through Simulink And Arduino Platform - Mitchelle, Law Jyy Jinn (Universiti Sains Malaysia, 2019)
The purpose of the thesis is to employ PID control system for thermal management and to evaluate the performance of the PID control system. This is carried out through the control of temperature of the Alternating Current (AC) lightbulb with the aid of MATLAB Simulink, Arduino, Solid-State Relay (SSR) and TMP36 temperature sensor. The proportional, integral and derivative parameters are examined in a range of values to achieve temperature set point of 60°C. From the investigations, the suitable values for Kp, Ki and Kd are, respectively, chosen based on their tendency to give negligible steady state error, less rise time, less settling time, good stability and no overshoot or undershoot. Through the observation, higher proportional gain contributes to less rise time, settling time and steady state error. Meanwhile, integral controller can eliminate the steady state error. High integral value will cause overshoot and undershoot as well as increases the settling time. Next, derivative controller is added to improve stability of the system. Higher derivative value shows better stability. For this experiment, Kp=10, Ki=0.02 and Kd=5 is deemed suitable and these values are employed to simulate thermal management for this setup for different temperature set points at 50°C, 70°C and 80°C on the AC lightbulb. All the set points can be achieved with no steady state error, good rise time, good settling time, no overshoot, no undershoot and good stability. The, trial and error PID tuning method is considered as less complicated and less analytical way compared to the existing tuning methods.